199k views
5 votes
Please help me solve these questions

Evaluate step by step

g(-2)=x^2+3X+2


And


g(3.14)=x^2+3X+2

User Munin
by
4.6k points

1 Answer

5 votes

Answer:

g(-2) = 0

g(3.14) = 21.2796

Explanation:

Simply substitute the values for x.

Step 1: Find g(-2)

g(-2) = (-2)² + 3(-2) + 2

g(-2) = 4 - 6 + 2

g(-2) = -2 + 2

g(-2) = 0

Step 2: Find g(3.14)

g(3.14) = (3.14)² + 3(3.14) + 2

g(3.14) = 9.8596 + 9.42 + 2

g(3.14) = 19.2796 + 2

g(3.14) = 21.2796

User Madiyaan Damha
by
4.9k points